STRATEGI PETANI GUREM DALAM PENANGGULANGAN KEMISKINAN MELALUI PERMINTAAN KREDIT DI KABUPATEN KAMPAR PROVINSI RIAU - Caska, Caska (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2010)
The research is purposed to understand the factor determining a credit demand and the efficiency level of the using of production factor. The research method used is explanatory survey method. We have 120 level scale farmers of oil palm as the customers, consists of 60 customers in both Mandiri bank and KUD. The results shows that: first, there is a connection according to a credit demand,we will have the level elasticity of interest rate of credit Â as -0,248; the elasticity of administration expense as 0,217; the elasticity of permanent income as 0,739; and the elasticity of transitory income as 0,077. Second, the factor of work force production in the decreasing returns to scale position, it means that the amount of oil palm production will increase with lower proportion than the increasing of work force expanse; and the financial capital factor in the increasing returns to scale, it means that the amount of oil palm production will increase with higher proportion than the increasing of financial capital.